An unusual presentation of solid variant ABC: A case report - S.R. Akhil; Sreeraj Rajan; Subin Sugath (Journal of Orthopaedic Reports)
Introduction: Solid variant ABC is a type of tumor that is rare and mostly found in the metaphysis of long bones. Its rarity makes it difficult for pathologists and radiologists to accurately diagnose this entity. This can create a dilemma for surgeons when deciding on the best treatment for the patient. We recently treated a case of Solid ABC with limb salvage surgery and are reporting on the successful outcome. Case presentation: A 41-year-old male patient presented with an expansile osteolytic lesion involving the upper-mid diaphysis of the left tibia with soft tissue involvement. Histopathological examination showed a tumour with many osteoclastic giant cells with sparse mitosis, favouring a diagnosis of a solid variant of aneurysmal bone cyst. The patient underwent a wide local resection + extracorporeal radiotherapy and plate osteosynthesis. Postoperative period was uneventful and there was no post-operative complications. Patient is having satisfactory functional outcome till the last follow-up, with no evidence of disease. Conclusion: When evaluating osteolytic lesions in long bones, it is important to include solid variant Aneurysmal Bone Cyst in the list of possible differential diagnoses, despite its rarity. Radiologically and histologically, these tumors have similar characteristics. Therefore, a treatment strategy that prioritizes safe radical resection will result in a better outcome.